FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PROGRAM PELAYANAN LANJUT USIA (POSYANDU LANSIA) - Rias Prasasti Oktafera; Ennimay Ennimay; Ahmad Hanafi (STIKES BHAMADA SLAWI, 2022)
Posyandu for the elderly is a place for health services for the elderly. Utilization of the Posyandu lansia in the working area of the Tapung II Health Center in 2019 is still low at 71.6% of the 100% Minimum Service Standard (SPM). The purpose of this study was to analyze factors related to the utilization of the Posyandu lansia in the Tapung II Puskesmas Working Area, Kampar Regency in 2021. This type of research was quantitative analytic using a cross sectional design. The population is all pre-elderly and elderly people in Tapung II Village, Kampar Regency, amounting to 817 people while the research sample is 86 people. Sampling was done by simple random sampling using a questionnaire as a data collector for the variables Knowledge, Attitude, Access to the Posyandu lansia, Family Support, Role of Cadre. Data analysis with chi square and multiple logistic regression. The results showed that the utilization of the Posyandu lansia in Tapung II Village, Tapung District, Kampar Regency was 86%. The results of multivariate analysis showed that the variables that influenced the use of posyandu lansia were knowledge (p=0.006) Attitude (p=0.007), family support (p=0.003), and the role of cadres (p=0.014). The most dominant variable influencing is family support (POR 36,744). The conclusion in this study is that there is a relationship between knowledge, attitudes, family support and the role of cadres on the utilization of services for the elderly service program at the Tapung II Health Center, Kampar Regency.